Reproductive Health Education in Preventing HIV/AIDS With Comics on Knowledge and Attitudes of Junior High School Students - Naila Fariha; Dimas Dwi Yoga S.; Jupriyono (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: In Malang city HIV/AIDS cases in 2022 there were 481 HIV cases, and 119 AIDS cases found. HIV/AIDS is one of the reproductive health problems that can be transmitted. So that education is needed since adolescence to prevent HIV/AIDS. Objective: This study aims to determine the effect of reproductive education using comic media on students' knowledge and attitudes in preventing HIV/AIDS. Method: This type of research is quantitative, with a pre-Experimental research method using a one group pretest-posttest approach, with a sample of 74 students of SMP 13 Malang City selected by probability random sampling technique. Result: The results of the study obtained a difference in knowledge after education with an majority of students are in the good category (100%) compared to before education, the majority are in the less category (90%). In the attitude of students there is an increase after being given education the majority in the positive category (59%), compared to before education in the positive category (54%). Based on the results of the analysis of the effect of reproductive health education with comic media on knowledge (p = 0.000), and on attitudes (p=0.000). Conclusion: Based on the results of the analysis, it was concluded that Ho was rejected, so there was an effect of reproductive health education with comic media on students' knowledge and attitudes in preventing HIV / AIDS